Resolving meaning conflict in translation: An optimality approach to verse translation - Dols, Nicolau; Mansell, Richard (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article proposes an application of Optimality Theory (Prince and Smolensky 1993) to translation analysis, suggesting that the translation process is regulated by a hierarchy of universal yet violable constraints. The constraints are always present but in conflict: strategies are determined by their hierarchy, and a constraint can be violated but only to avoid violation of a more highly-ranked constraint, i.e. a prioritised form of transfer. Optimalist concepts present in the literature are surveyed, and after a series of examples the authors propose that an optimalist approach reveals translators’ strategies and their basis both at a micro- and textual level, a theoretical basis for a multi-layer unit of translation, a cognitive basis for Toury’s two laws of translation, and they suggest that there are no others.